Surgical Parameters Related to Excessive Intrarenal Pressure during Minimally Invasive Percutaneous Nephrolithotomy in the Supine Position: A Prospective Observational Clinical Study. (12th July 2022) - Jung, Gyoohwan; Kho, Yongseok; Park, Jae Suk; Yuk, Hyeong Dong; Ryang, Seung Hoon; Cho, Sung Yong
Abstract : Objective . Excessive intrarenal pressure (IRP) during surgery for renal stones is related to postoperative complications due to systemic absorption of bacteria and endotoxins. This study is aimed at evaluating factors that induce excessive IRP in minimally invasive percutaneous lithotripsy (mini-PCNL) in the supine position. Methods . 27 patients underwent mini-PCNL for intrarenal stones under supine position and were analyzed in this study. The IRP changes were measured at the phases of "baseline, " "table tilting, " "upper-pole navigation, " "stone fragmentation, " and "vacuum cleaning effect." The relationship between the mean IRP and cumulative time of IRP ≥ 30  cmH2 O was analyzed by according to the surgical parameters. Multiple regression analysis showed the effect of the surgical parameters on postoperative fever-related IRP elevation. Results . Mean age was 59.3 ± 14.6 years. The mean stone burden was 24.6 ± 8.1  mm 3 . IRP was higher than baseline (31.6 ± 12.1 ) during upper-pole navigation (60.0 ± 22.9, p = 0.003 ) and stone fragmentation (46.2 ± 9.9, p < 0.001 ). The subgroup's IRP baseline < 20  cmH2 O significantly increased during the upper-pole navigation. Changes in IRP at each stage were affected by baseline IRP (p < 0.001 ), operation methods (p = 0.021 ), number of calyces with stones (p = 0.034 ), and laser energy of Joules (p = 0.041 ) and frequency (p = 0.038 ). Conclusion . In supine mini-PCNL, the IRP was higher during laser fragmentation and upper-pole navigation. The table tilting procedure can be helpful in selected patients. The vacuum cleaner effect did not affect IRP.